UJI EFEKTIFITAS JAMUR ENTOMOPATOGEN Lecanicillium lecanii Zimm. TERHADAP LARVA GRAYAK Spodoptera exigua Hubner PADA TANAMAN BAWANG MERAH Allium ascalonicum L - Ria Astari Putri (Jurnal Ilmiah Hijau Cendekia, 2023)
Shallots (Allium ascalonicum L) are one of the horticultural crops that have received attention from both the public and the government and shallots are one of the crop commodities that have high economic value and are widely cultivated by farmers in the lowlands. Indonesia is an attack of harmful plant-disturbing organisms (OPT). The main problem in onion cultivation is the onion caterpillar pest Spodoptera exiguaShallots (Allium ascalonicum L) are one of the horticultural crops that have received attention from both the public and the government and shallots are one of the crop commodities that have high economic value and are widely cultivated by farmers in the lowlands. Indonesia is an attack of harmful plant-disturbing organisms (OPT). The main problem in onion cultivation is the onion caterpillar pest Spodoptera exigua. This study was arranged using a Completely Randomized Design (CRD) with 5 treatments each and repeated 4 times. Each experimental unit consisted of 10 S. exigua instar 3. Treatment consisted of (P0) control treatment (P1) Treatment density 106 conidia/ml, (P2) Treatment density 107 conidia/ml, (P3) Treatment density 108 conidia/ml , (P4) Treatment density was 109 conidia/ml. S. exigua used for the application found 10 tails each. Observation variables used: mortality, mycosis, length of time mycosis, mummification and mummification time.The results showed that the use of entomopathogenic fungus L. lecanii had a significant effect on mortality of S. exigua, namely the most effective concentration was found in the treatment concentration of 109 konidia/ml with a mortality value of 62.5%. 80.95% and 98.33% mummification percentage. However, the fast results for S. Exigua mycosis were shown at a concentration of 108 conidia/ml and 109 conidia/ml, namely 1.06 days (Bar Chart 4.3) and the long time results for S. Exigua mummification were shown at a concentration of 107 conidia/ml, which was 4 days. while the treatment that had the fastest time for mummification was with a concentration of 109 conidia/ml which was 1.81 days and the use of entomopathogenic fungus L. lecanii could affect the mummification of S. exigua, the highest yield was indicated by a concentration of 109 conidia/ml, which was 98.3% (Bar Chart 4.4). while the treatment with the lowest mummification with a concentration of 106 conidia/ml is 75%.